2017
DOI: 10.1002/eji.201646806
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐γ directly inhibits murine B‐cell precursor leukemia‐initiating cell proliferation early in life

Abstract: The early-life immune environment has been implicated as a modulator of acute lymphoblastic leukemia (ALL) development in children, with infection being associated with significant changes in ALL risk. Furthermore, polymorphisms in several cytokine genes, including IL-10 and IFN-γ, are associated with leukemia development. However, the mechanisms and timing of these influences remain unknown. Here, we use the Eμ-ret transgenic mouse model of B-cell precursor ALL to assess the influence of IFN-γ on the early-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…There is a literature on the impact of inflammatory cytokines on hematopoiesis that shows interferon-gamma inhibits normal hematopoiesis (43). There is conflicting literature on the effect on malignant B cells with some reports showing impairment (44) others showing growth enhancement (45). Our data suggest that in the setting of allogeneic transplant the net effect is impairment of malignant B cell survival with both the cytokines and cyclosporine contributing to leukemia cell death.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…There is a literature on the impact of inflammatory cytokines on hematopoiesis that shows interferon-gamma inhibits normal hematopoiesis (43). There is conflicting literature on the effect on malignant B cells with some reports showing impairment (44) others showing growth enhancement (45). Our data suggest that in the setting of allogeneic transplant the net effect is impairment of malignant B cell survival with both the cytokines and cyclosporine contributing to leukemia cell death.…”
Section: Discussionmentioning
confidence: 73%
“…The mechanisms for the graft versus leukemia are not fully known. Much of the literature has focused on T cell and NK cell antileukemia cytolytic activity, although some studies have pointed to a role for interferon gamma (44,(47)(48)(49). In our system, we asked the question of whether the changes in ALLs induced by the cytokines and cyclosporine would change their sensitivity to allogeneic cytolytic cells.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that IFN‐γ causes early proliferation impairment, as a direct effect on B‐ALL cells, in addition to immune‐mediated effects on the more immunogenic subclones (Fidanza et al , 2017). This “equilibrium phase” is followed by an “escape phase” where less immunogenic and more aggressive B‐ALL subpopulations are selected.…”
Section: Discussionmentioning
confidence: 89%
“…The analysis of biomarker signatures further supports these findings ( Figures 2 and 5 ). It has been proposed that while cytokine levels may influence leukemia progression at multiple time points during disease development, other studies have suggested a relevant early influence of basal cytokine production on leukemogenesis ( 22 ). Nevertheless, studies of chemokines and cytokines in B-ALL that focus on prognostic markers are still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies of chemokines and cytokines in B-ALL that focus on prognostic markers are still scarce. Research using murine models have demonstrated that the absence of IFN-γ results in higher numbers of leukemia-initiating cells and accelerated leukemia onset ( 22 ).…”
Section: Discussionmentioning
confidence: 99%